ANALISIS KESULITAN BELAJAR SISWA PADA PROSES PEMBELAJARAN BIOLOGI KELAS X SMA PGRI PEKANBARU - Melia Tri Lestari; Darmawati Darmawati; Arnentis Arnentis (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to determine the learning difficulties of students in the biology learning process of class X SMA PGRI Pekanbaru. This type of research is a descriptive study. The research was conducted at SMA PGRI Pekanbaru from November to December 2019. The sampling technique used the total sampling technique so that the sample in the study, namely class X IPA SMA PGRI Pekanbaru were 30 students and class X IPS SMA PGRI Pekanbaru were 30 students in total. a total of 60 students. Collecting data using questionnaire distribution techniques and data collection instruments using a questionnaire. The questionnaire trial data was tested for validity and reliability using the SPSS software program. The results showed that the average indicator of internal factors causing learning difficulties in biology class X IPS SMA PGRI Pekanbaru was 71% in the